The Means Of Verbalization Of Non-Verbal Communication Acts In Fiction Texts Of Modern German Literature - Zueva, Elena (2018)
The article presents the results of study of acts and functions of behavioral communication that can be found in fiction and descriptive modeling of stereotype means of their verbalization in modern German. Only a limited number of models, which represents extra-linguistic communicative components, were discovered. They can be added to optional lexical elements reflecting the specificity of recipient’s perception of the act. Contextual conditionality of verbalization of non-verbal components is determined by a number of functions which they perform interacting with verbal message in a dialogue. Autonomic usage of paralinguistic means is used for expression of emotional and mental state of participants of communication.